IDENTIFICATION OF SOCIAL SKILLS IN LATE ADOLESCENTS TAKING VOCATIONAL SCHOOL EDUCATION IN THE CITY OF BEKASI - Widyaningrum, Intan; Marsidi, Sitti Rahmah (LP2M IAI Al-Khairat Pamekasan, 2024)
The aim of this research is to obtain an overview of the social skills of late adolescents studying vocational school in Bekasi City. This research is descriptive quantitative research with a purposive sampling technique. The research sample consisted of 100 finalist teenagers studying vocational school in Bekasi City. The social skills measuring tool has 19 valid items and a reliability value of 0.904. The results of the research show that there are more teenagers taking vocational high school education in Bekasi City with a high level of social skills (56%), compared to low social skills (44%). The highest percentage of those with high social skills were found in late teens taking vocational school education in Bekasi City, male (56.5%), 16 years old (67.9%), 10th grade (67.9%), and from the City Vocational School area. West Bekasi (100.0%). The highest percentage of those with low social skills were found in late teens taking vocational school education in Bekasi City, female (44.4%), 18 years old (50.0%), 12th grade (48.8%), and from the Bekasi City Vocational School area. north (53.5%).